Comparison of inshore and offshore fish larval assemblages within the wider Yangtze River estuary (China). (25th November 2015) - Jiang, M.; Li, L.; Shen, X. Q.; Quan, W. M.
Summary: It is hypothesized that fish larvae undertake vertical movements in estuarine waters. To test this hypothesis, a sampling period was selected during times when many spring‐spawning fish reach maximum abundance in coastal waters so that spring and summer variations in larval fish assemblages could be determined in the Yangtze River estuary. Six oceanographic surveys were conducted across the salinity gradient of an inshore (freshwater) and offshore area (brackish intersection) during spring (May) and summer (August) between 2010 and 2012. The fish larval community was dominated by species of Engraulidae, Gobiidae, Champsodontidae and Mugilidae. The pre‐flexion and flexion larval stages of euryhaline marine species, which are dependent on estuaries as nursery areas, were common. The brackish and marine larval assemblage was the most abundant with taxa such as Coilia mystus and Engraulis japonicus accounting for more than 57.3% of the total catch. Spatial differences in the taxonomic composition of larval fish assemblages were evident between the inshore and offshore areas. Additionally, the Yangtze River runoff regulatory functions as affected by the Three Gorges Reservoir operational mode (hydrological alternating operations) showed weak influences on fish and habitat environments. Low salinities from high freshwater inflow limited bay anchovy production in the inshore area.